Implikasi Artificial Intelligence (AI) Pada Profesi Auditor : A Systematic Literature Review - Afi Syasya Safa Maharani; Totok Dewayanto (Diponegoro Journal of Accounting, 2026)
The advancement of Artificial Intelligence (AI) has driven significant transformation in auditing practices. AI's ability to process large-scale data, detect anomalies, and perform predictive analysis offers opportunities to enhance audit efficiency, accuracy, and quality. However, AI adoption also introduces new challenges related to the professionalism and ethics of the auditing profession, such as algorithmic bias, competency limitations, and potential reductions in accountability. This study aims to analyze the implications of AI use on audit process efficiency, auditor professionalism, and audit ethics. The research method used is a Systematic Literature Review (SLR) of scientific articles published between 2020 and 2025 through the Scopus database. The results indicate that AI can improve the efficiency of audit procedures through automated data testing and real-time risk detection, while also requiring auditors to develop technological competencies and higher professional skepticism. On the other hand, risks such as algorithmic bias, lack of system transparency (black box), and unclear accountability pose ethical challenges that need to be anticipated. These findings underscore the need for regulatory frameworks, ethical guidelines, and specialized training programs to ensure that the use of AI supports audit quality without compromising fundamental professional values such as integrity, objectivity, and independence. This study is expected to serve as a reference for academics, audit practitioners, and policymakers in formulating technology adaptation strategies and future research directions.